Asymmetry in the Prediction of Cojumps on Volatility and Its Reversal - Liling Deng; Zhiqiang Wang; Haifang Xiong (Discrete Dynamics in Nature and Society, 2022)
The asymmetry of volatility is an important feature of asset price changes, and studying the asymmetry of cojumps on volatility prediction can provide a reference for systemic risk monitoring. Based on high-frequency data of CSI 300 stock index and futures index, SSE Composite Index, and industry index, the influence of cojumps on volatility in different directions is analyzed by HAR model. It is found that the explanation of volatility by cojumps still has leverage effect, and the symbolic cojumps covariance can obviously improve the prediction ability of the model; influenced by policy reform and market changes, the prediction of cojumps on volatility between the CSI 300 stock index and futures index shows a significant interval reversal effect; not only is the prediction of systematic cojumps on volatility of each industry index related to the periodicity of the industry, but also it shows different rules under the influence of policy reform.